Alcohol Use and HIV Disease Progression in an Antiretroviral Naïve Cohort - Hahn, Judith A.; Cheng, Debbie M.; Emenyonu, Nneka I.; Lloyd-Travaglini, Christine; Fatch, Robin; Shade, Starley B.; Ngabirano, Christine; Adong, Julian; Bryant, Kendall; Muyindike, Winnie R.; Samet, Jeffrey H. (Journal of acquired immune deficiency syndromes, 2018)
Alcohol use has been shown to accelerate disease progression in experimental studies of simian immunodeficiency virus in macaques, but the results in observational studies of HIV have been conflicting. We conducted a prospective cohort study of the impact of unhealthy alcohol use on CD4 cell count among HIV-infected persons in southwestern Uganda not yet eligible for antiretroviral treatment (ART). Unhealthy alcohol consumption was 3-month Alcohol Use Disorders Identification Test – Consumption (AUDIT-C) positive (≥3 for women, ≥4 for men) and/or phosphatidylethanol (PEth - an alcohol biomarker) ≥50 ng/ml, modeled as a time-dependent variable in a linear mixed effects model of CD4 count.
Keywords: HIV progression; Phosphatidylethanol; Sub-Saharan Africa; Antiretroviral adherence